Graphene oxide and its application as an adsorbent for wastewater treatment. Issue 2 (4th October 2013) - Kyzas, George Z.; Deliyanni, Eleni A.; Matis, Kostas A.
Abstract Graphene oxide, particularly as magnetic particles, has recently been used as an adsorbent for wastewater treatment in applications such as heavy metals separation (mercury, cadmium, copper, chromium, arsenic) and also organics (antibiotics, dyes, i.e. Reactive black 5, etc.). Selected examples will be given in the present review—mostly from the literature. The following themes are examined among others: the synthesis route (impregnation, co‐precipitation), kinetics of adsorption, thermodynamics, isotherm studies and applications in comparison with other adsorbents. © 2013 Society of Chemical Industry